The advocacy trap : transnational activism and state power in China - Noakes, Stephen (Alternative sinology., 2018)
This book asks what happens to transnational civil society actors as a result of their engagement with China, recognizing its status and influence as a rising world power as both real and meaningful. Taking an interactive and processed-based approach, it aims to explain the multiple, divergent pathways or functional forms of advocacy campaigns in China.